METODE DE ANALIZĂ UTILIZATE ÎN DETERMINAREA CONTAMINĂRII CU METALE GRELE (PANGEEA, 2025)
Analytical methods used to determine contamination with heavy metals. This paper work approaches some methods of analysis used for determination of the heavy metal pollution degree. The paper describes a few essential methods and applications of assessing the heavy metal and other toxic compounds. We refer also to spectrometric method, starting from some general aspects of these, approaching then the characteristics and the applications of method.